Isolation and Characterization of the Fertility Factor P of Vibrio cholerae - Datta, Archana (1973)
Vibrio cholerae strains with the transmissible fertility factor P contained a supercoiled circular deoxyribonucleic acid (DNA) component amounting to between 2 and 6% of the total DNA obtained from the cells. Such a component was not observed in V. cholerae strains lacking the fertility factor. This supercoiled circular DNA was isolated from P(+) cells, and the molecular weight was determined by sedimentation velocity experiments and electron microscopy to be approximately 80 million daltons. These supercoiled circular DNA molecules, which have a guanine plus cytosine (G + C) composition of 42%, were concluded to be the extrachromosomal P factor. It was calculated that there is approximately one copy of the P factor per chromosome. A small amount of supercoiled circular DNA was occasionally isolated from the P(−) strains of V. cholerae. The function of this component, which has a molecular weight of 40 million daltons, is not known. The molecules found in the P(−) strains were readily distinguished from the P(+) circular molecules by their smaller molecular weight and different G + C composition.